THE INFLUENCE OF AFFIRMATION TECHNIQUES ON THE LEVEL OF ANXIETY OF PREGNANT WOMEN IN THE III TRIMESTER IN FACING LABOR AT THE DUREN SAWIT HEALTHY PREGNANCY CLINIC YEAR 2023 - Andriyani, Yesi Dwi (HEARTY, 2025)
Pregnancy is an important period in a woman’s life. In the third trimester of pregnancy, a number of maternal fears will arise. The Affirmation Technique is considered positive for improving the psychological problems of pregnant women such as stress and anxiety experienced by pregnant women in the third trimester. This study aims to determine the effect of providing affirmation relaxation techniques on the level of anxiety of pregnant women in the third trimester when facing childbirth at the Duren Sawit Healthy Pregnancy Clinic. This research uses a quasi-experimental type of research, with a pretest and posttest research plan with a control group. sample of 34 respondents with purposive sampling. This research was conducted at the Duren Sawit Healthy Pregnancy Clinic. The research instrument used the Hamilton Anxiety Rating Scale (HARS) questionnaire. Data analysis uses the dependent T test. The research results show that there is an influence of affirmation techniques on the level of anxiety in pregnant women in the third trimester when facing childbirth at the Duren Sawit Healthy Pregnancy Clinic in 2023 (p = 0.000). It is hoped that this can provide input for health service agencies, especially the Duren Sawit Healthy Pregnancy Clinic, East Jakarta, regarding the benefits of affirmation techniques for the anxiety of pregnant women in the third trimester when facing childbirth.